Mucking Around in Class, Giving Crap, and Acting Cool: Adolescent Boys Enacting Masculinities at School - Martino, Wayne (Canadian Journal of Education/Revue canadienne de l'éducation, 2000)
Semi-structured interviews with adolescent boys attending a Catholic coeducational high school in Perth, Western Australia, were analyzed using a Foucauldian approach to establish how these boys relate to one another and respond to their experiences of schooling. Their rejection of academic achievement and their peer group relations are tied to acting out problematic forms of “cool” masculinity. The ability of some boys to identify the social dynamics and the consequences of their behaviour for themselves and others suggests entry points and thresholds for school programs in masculinity education. Des entrevues semi-dirigées auprès d’adolescents fréquentant une école secondaire mixte catholique à Perth, Westerm Australia, ont été analysées à l’aide d’une approche foucauldienne afin de déterminer le type de relations qu’entretiennent ces garçons entre eux et leurs réactions aux expériences scolaires. Leur rejet de la réussite scolaire et leurs relations avec leurs pairs sont reliés à des comportements problématiques de masculinité jugés « chics ». La capacité de certains garçons d’identifier la dynamique sociale et les conséquences de leur comportement sur eux- mêmes et autrui permet d’envisager des points d’entrée pour des programmes scolaires portant sur la masculinité.